Influence of thermodynamic disfigurement on the convective heat transfer of solar greenhouse - Sun, Yachen; Cao, Yanfei; Wang, Haotian; Zhou, Changji; Xiao, Jinxin; Jiang, Chengyao; Li, Jianming; Bao, Encai; Zou, Zhirong (International Journal of Agricultural and Biological Engineering, 2020)
Solar greenhouse is a typical greenhouse without any additional heating system, which has developed rapidly in Northern China. However, due to the construction quality, management methods, especially the long-term use and other factors, there are usually different degrees of thermodynamic disfigurements in the envelop enclosure of solar greenhouse. The purpose of this study was to investigate the influences of thermodynamic disfigurement on the temperature distribution and convective heat transfer of solar greenhouse. In this study, the east and west compartments of a typical solar greenhouse which is located in Yangling, China (108°4′E, 34°16′N) were tested. The air temperature of each compartment was collected using temperature recorders, and the thermal infrared images of different compartment envelopes were obtained by a thermal infrared imager on a typical cloudy day. Convective heat transfer coefficients and heat flux densities of different compartment envelopes in the solar greenhouse were calculated. The results showed that the temperature difference can be displayed in the thermal infrared images of compartment envelopes, the surface temperature of the front roof was the lowest, followed by the back roof, the wall surface temperature was the highest. The minimum average surface temperature of the front roof in the eastern compartment was only 3.8°C, which was 6.8°C and 9.2°C lower than the average surface temperature of the back roof and back wall, respectively. The surface average temperature of thermodynamic disfigurements located at the bottom of the south side in the front roof of the eastern compartment, whose area accounted for 16.5% of the total front roof in the eastern compartment, was only 5.4°C. Compared with non-thermodynamic disfigurement, the average convective heat transfer coefficient and heat flux density of thermodynamic disfigurements in the front roof of the eastern compartment were increased by 20.3% and 110.3%, respectively. The average air temperature in the eastern compartment was 3.5°C lower than the average air temperature in the western compartment of the solar greenhouse. Construction of brick wall at the bottom of the south side of the front roof in the solar greenhouse helped to increase the inner surface temperature of the front roof, with an average temperature rise of 6.2°C, and reduce the area of thermodynamic disfigurement, which only accounted for 2.6% of the total front roof in the western compartment. The average surface temperature of thermodynamic disfigurements mainly caused by the entry and exit door in the wall of the eastern compartment was only 9.8°C, which was lower 3.2°C than the average temperature of non-thermodynamic disfigurement of the wall. Thermodynamic disfigurement helped to increase heat loss. The weighted average proportion of thermodynamic disfigurement in the western compartment was 2.1%, while that of thermodynamic disfigurement in the eastern compartment was 10.7%. The thermal insulation performance of the western compartment envelope in the solar greenhouse was better than that of the eastern compartment envelope. Keywords: solar greenhouse, thermodynamic disfigurement, convective heat transfer, thermal infrared image DOI: 10.25165/j.ijabe.20201304.5397 Citation: Sun Y C, Cao Y F, Wang H T, Zhou C J, Xiao J X, Jiang C Y, et al. Influence of thermodynamic disfigurement on the convective heat transfer of solar greenhouse. Int J Agric & Biol Eng, 2020; 13(4): 55–60.